The Influence of Knowledge Sharing and Empowerment on Employee Performance in All Branches of Threeleanor Aesthetic Clinic: Penelitian - Charlene Siswara (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the effect of knowledge sharing and empowerment on employee performance in all branches of Threeleanor Aesthetic Clinic. The research approach used is quantitative with survey techniques. Data collection was carried out through questionnaires distributed to employees of Threeleanor Aesthetic Clinic and analyzed using SPSS. The results of the study indicate that Knowledge Sharing and Empowerment have a positive and significant effect on employee performance. Then based on the results of the partial determination coefficient test, it can be concluded that the most dominant variable in influencing employee performance is Empowerment. The results of this study provide practical implications for the management of Threeleanor Aesthetic Clinic, especially in developing human resources and supporting the sustainability of the company's business.